Prenatal and Postnatal Development of the Stomach in Wistar Albino Rats (Annals of Medical Research, 2021)
Aim: In this study, histological changes in stomach during prenatal and postnatal development were examined.
Keywords: Development; Stomach; Prenatal; Postnatal.